Understanding the cadastre in rural areas in Poland after the socio-political transformation. Issue 1 (2nd January 2019) - Noszczyk, Tomasz; Hernik, Józef
Abstract: The paper looked into the issue of the validity of the cadastral data for rural areas in Poland after the socio-political transformation in 1989. Hence, the current state of the cadastral data and its consequences were discussed. The aim of this paper was to present the update status of cadastral data for rural areas in Poland, to describe a model example of cadastre modernisation (a case study of Michałowice) and to stress the necessity of 'active cadastre-keeping' in future. Analyses were based on a model example of cadastre modernisation and assessment of its results in the rural Municipality of Michałowice, Poland. Reasons for the decision of the local authorities to modernise the cadastre, society response, and positive and negative aspects of the modernisation were discussed. The authors stress the fact that future passive keeping of real estate cadastre by the authorities may entail outdated data despite any past modernisations.